Silencing the gip gene of Phytophthora cinnamomi by iRNA and studying the subcellular localization of GIP and NPP1 proteins - Chahed, Abdessalem (2016)
Mestrado com dupla diplomação com o High Institute of Biotechnology of Monastir (ISBM), Tunisia